2014
DOI: 10.1016/j.ccr.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The PRKCI and SOX2 Oncogenes Are Coamplified and Cooperate to Activate Hedgehog Signaling in Lung Squamous Cell Carcinoma

Abstract: SUMMARY We report that two oncogenes co-amplified on chromosome 3q26, PRKCI and SOX2, cooperate to drive a stem-like phenotype in lung squamous cell carcinoma (LSCC). PKCι phosphorylates SOX2, a master transcriptional regulator of stemness, and recruits it to the promoter of Hedgehog Acyl Transferase (HHAT), which catalyzes the rate-limiting step in Hh ligand production. PKCι-mediated SOX2 phosphorylation is required for HHAT promoter occupancy, HHAT expression, and maintenance of a stem-like phenotype. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
292
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(303 citation statements)
references
References 67 publications
10
292
0
1
Order By: Relevance
“…Justilien et al first reported a mechanism by which PRKCI forms a complex with ECT2-PAR6A to drive transformed growth through activation of a RAC1-PAK-MEK1-ERK1,2 signaling axis in NSCLC (14,25). Recently, the same group reported a functional link of PRKCI and SOX2 to activate hedgehog signaling in lung SCC (30 We also demonstrate that although genomic amplification is a key mechanism of FXR1 gene overexpression, it is the gene expression level that drives tumor progression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Justilien et al first reported a mechanism by which PRKCI forms a complex with ECT2-PAR6A to drive transformed growth through activation of a RAC1-PAK-MEK1-ERK1,2 signaling axis in NSCLC (14,25). Recently, the same group reported a functional link of PRKCI and SOX2 to activate hedgehog signaling in lung SCC (30 We also demonstrate that although genomic amplification is a key mechanism of FXR1 gene overexpression, it is the gene expression level that drives tumor progression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Although criteria for their characterization have been proposed [37], particularly for amplified genes, they stipulate multiple lines of independent evidence which require considerable resources and, as such, have not been generated for most loci. Moreover, it is possible that in some instances where a minimal region of amplification contains more than one gene, such as the 11q13/14 locus which defines IntClust 2, that adjacent genes may act in a concerted manner to confer a selective growth advantage just as has been observed in lung cancer [38]. The conception of IntClust was pragmatic in attempting to minimize the influence of passenger genes.…”
Section: Deletionsmentioning
confidence: 99%
“…18,25 Shh signaling involves carcinogenesis, drug resistance, and poor prognosis of various types of cancers. [26][27][28] In this study, we determined that IR might activate Shh signaling to protect cancer cells. Accordingly, synthetic Shh peptides protected human glioblastoma cells from IR-mediated death.…”
Section: Discussionmentioning
confidence: 99%